Lead Poisoning in Gurkha Soldiers in Hong Kong. Issue 5666 (9th August 1969) - Power, J. G. P.; Barnes, R. M.; Nash, W. N. C.; Robinson, J. D.
Abstract : Investigation of an outbreak of lead-poisoning in 121 Gurkha soldiers showed that this was due to the contamination of chilli powder (cayenne pepper), a constituent of curry powder, with lead chromate. Comprehensive systems of food sampling are needed in developing communities.